Ethics after intervention: should warlords be empowered as statesmen? - Daniel Duarte Flora Carvalho (Ethic@: an International Journal for Moral Philosophy)
Since the end of the Cold War, when the number of peacekeeping and peacebuilding interventions considerably increased, the debate about their ethics raised as an important aspect regarding both its ends and its means. Literature was roughly divided between those who advocated for an approach centred on global actors, liberal peace and cosmopolitanism and those who stood for the role of local actors and indigenous solutions for the problems in question. In this regard, the relationship that the International Community usually held with warring parties in civil conflict came to the fore. This essay looks forward to providing insights about the role that warlords can play in facilitating and hindering internationally-led peace process. Using Burundi and Somalia as case-studies, it is argued that warlords can only commit to liberal and cosmopolitan ethics after the state institutions have been built and solidified.